An update of a former FIGO Working Group Report on Management of Posterior Compartment Prolapse. Issue 2 (19th November 2019) - Doumouchtsis, Stergios K.; Raheem, Ali Abdel; Milhem Haddad, Jorge; Betschart, Cornelia; Contreras Ortiz, Oscar; Nygaard, Christiana C.; Medina, Carlos A.; La Torre, Fillippo; Iancu, George; Cervigni, Mauro; Zanni, Giuliano
Abstract: Background: The FIGO Working Group (FWG) in Pelvic Floor Medicine and Reconstructive Surgery (2012–2015) established a consensus among international opinion leaders in evaluating current evidence and providing practice recommendations. Objectives: To provide an update of the previous clinical opinion report on conservative and surgical treatment of posterior compartment prolapse. Search strategy: Search of evidence was performed using Pubmed, Embase, and Cochrane Library databases up to August 2018. Selection criteria: Controlled trials on posterior colporrhaphy, site‐specific defect, transanal, abdominal, laparoscopic, and mesh repair. Data collection and analysis: Collective consensus on surgical outcomes was based on a decision‐making process during meetings and multiple group consultations. Main results: Basic evaluation and conservative treatment precede surgical management. Surgical techniques are performed by vaginal, transperineal, transanal, abdominal, or laparoscopic approach. The transvaginal surgical route without mesh appears superior to the transanal route. No conclusions can be drawn based on clinical studies or randomized controlled trials of posterior colporrhaphy and laparoscopic rectopexy. Conclusions: Management of rectocele should include patients' history, quality of life questionnaires, and, in case of complex anorectal symptoms, imaging and functional studies. Evidence on the best type of posterior vaginal wall repair is still scarce. Randomized controlled trials are needed to determine the best approach to achieve safe, effective, and long‐term anatomical and functional outcomes. Abstract : Updated clinical opinion of the former FIGO Working Group report evaluating current evidence and providing practice recommendations on the treatment of posterior compartment prolapse.